Hydrometeorological Disaster: Challenges and Mitigation in Indonesia - Palsapah Aeni; Muhammad Khoirul Anwar (Jurnal Indonesia Sosial Teknologi, 2024)
Climate change, which includes increasing global temperatures, irregular rainfall patterns, and extreme changes in weather, has resulted in detrimental consequences for society and the economy, especially concerning an increase in hydrometeorological disasters. Indonesia is prone to natural disasters, primarily related to hydrometeorological events such as floods, landslides, and droughts. Hydrometeorological disasters can cause enormous economic and social losses; therefore, it is vital to holistically address climate change's social and economic impacts. This study aims to analyse trends in hydrometeorological disasters, especially in disaster-prone areas, so that the affected areas know comprehensive mitigation efforts to overcome them. The research methodology uses qualitative methods with descriptive analysis of hydrometeorological disasters in West Java and DKI Jakarta. The study results show that the trend of hydrometeorological disasters in West Java and DKI Jakarta Provinces tends to increase yearly. Several factors, including climate change, uncontrolled development, increasing population, topography and geographical location, and land subsidence, cause the latest disasters. The Indonesian government is actively trying to mitigate the risk of hydrometeorological disasters but is still experiencing some challenges, including topography and geographic location, climate change, limited resources, and low public awareness. Pentahelix collaboration and comprehensive public education are ways of overcoming these disasters. The Pentahelix collaboration allows for synergy between government, industry, and academia in identifying risks, formulating policies, and implementing mitigation programs.